1998
DOI: 10.1016/s0969-2126(98)00060-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing global substates of myoglobin

Abstract: Configuration space projections provide invaluable information about protein motions that would be extremely difficult to obtain otherwise. While the configuration space for myoglobin is quite large, it does have structure. Our analysis of this structure shows that the protein hops between a number of distinct global conformational states, much like the local behavior observed for an individual residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Dynamics of hbLBD-Proteins are known to be dynamic, and they sample numerous conformational states (67,68). The concept of a free energy landscape suggests that even the so-called native state of a protein is actually a statistical ensemble of different conformational substrates with similar free energies (69).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamics of hbLBD-Proteins are known to be dynamic, and they sample numerous conformational states (67,68). The concept of a free energy landscape suggests that even the so-called native state of a protein is actually a statistical ensemble of different conformational substrates with similar free energies (69).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the structures of the configurational space of Mb arise from the regular arrangement of relatively rigid a-helices [25]. Moreover, it was observed that even minute changes in the dynamical properties of the system alter the configurational space projection [25]. Therefore, we assigned to the same cluster those conformations that share most of their secondary structure motifs, i.e.…”
Section: Identification Of Representative Structures In the Trajectoriesmentioning
confidence: 99%
“…To solve that calculates distances between each node of the der identical conditions. The myoglobin simulation is regrid and each solute atom would be prohibitively ported in a separate paper, 31 and therefore, only a brief…”
Section: Distribution Functionsmentioning
confidence: 99%